Evaluating the Influence of Viral Marketing and Brand Awareness on Purchase Decisions a Study Tiktok Shop - Pane, Hartini Pratiwi; Napitupulu, Ismail; Luthfi, Syahrika; Situmorang, Syafrizal Helmi (Formosa Journal of Science and Technology, 2024)
This study examines the impact of Viral Marketing and Brand Awareness on Purchasing Decisions, individually and collectively. The quantitative study approach examines 90 consumers using the Tik Tok Shop in Tebing Tinggi. The sample was selected using a purposive sampling approach grounded in particular criteria. Data collection was conducted using an online questionnaire, and Data analysis was conducted via SPSS version 25. The findings indicated that Viral Marketing significantly influences Purchasing Decisions and Brand Awareness. Both Viral Marketing and Brand Awareness have a substantial and beneficial influence on Purchasing Decisions. This research enhances comprehension of The impact of digital marketing methods on consumer behavior in the era of social media.